The Behavioral Level of Emotional Intelligence and Its Measurement - Boyatzis, Richard E. (Frontiers in Psychology, 2018)
Emotional Intelligence (EI) is now widely used in organizations and graduate schools with an increase in published research supporting it. Discussion about EI whether based on measures or theory has given little distinction as to behavioral EI (i.e., how does EI appear in a person’s actions). This results in spurious conflicts about the validity of the different theories or measures which likely limit predicting managerial and leadership effectiveness, engagement, innovation and organizational citizenship. By adding a behavioral level, the concept of EI could relate to work and life outcomes beyond general mental ability and personality traits, avoid some of the criticisms while providing a more holistic theory of EI. As such, EI exists within personality as a performance trait or ability, and a self-schema self-image and trait, and a set of behaviors (i.e., competencies). The main contribution of this establishing the behavioral EI with a multi-level theory, while explaining how to assess it, the benefits of such a concept and its psychometric validity and challenges. The history and assortment of validation studies will illustrate that measures can rigorously and effectively assess the behavioral level of EI.